Influence of language proficiency, age and gender on academic performance - Ting, Su Hie; Musa, Muriatul Khusmah; Yong, Siaw Hua (2009)
The study investigates the relationship between language proficiency, age and gender on academic performance of undergraduates in a TESL degree programme. In this study, language proficiency was gauged using the Malaysian University English Test (MUET) band scores and academic performance using the Cumulative Grade Point Average (CGPA). Data from a questionnaire administered to 121 students enrolled in Years 1,2 and 3 of the TESL degree programme indicated a positive relationship between language proficiency and academic performance. Age and gender were found not to influence academic performance. The findings suggest that the academic success of university students is dependent on their mastery of the language of instruction. The implications of the findings on university entry requirements are discussed